Conifer root nodules colonized by arbuscular mycorrhizal fungi in Jurassic geothermal settings from Patagonia, Argentina - Nunes, Cristina Isabel (2019)
Premise of research. Despite the ecological significance of arbuscular mycorrhizae in modern terrestrial ecosystems, knowledge about their evolution based on the fossil record is still scarce, especially concerning the case of root nodules harboring arbuscular mycorrhizal fungi, as in some extant gymnosperms and angiosperms. Exceptionally preserved conifer nodular roots were found in the Jurassic fossil-bearing chert deposits of the Deseado Massif (Santa Cruz, Argentina), raising the possibility of studying them in association with arbuscular mycorrhizal fungi. The aim of this study is to describe the plant organs and their fungal partners and to discuss the ecological significance of the interactions observed, particularly with respect to their occurrence in the hot spring settings. Methodology. Thin sections of chert samples from the Cañadón Nahuel locality of the La Matilde Formation, Deseado Massif (Santa Cruz, Argentina) were observed using light microscopy. Pivotal results. The cortex of the nodules is occupied by several glomeromycotan fungal structures. The structures occur in a specific zone of the cortex—toward its center—and include intracellular hyphal coils and arbuscules. Glomoid spores and coenocytic hyphae possibly penetrating the epidermal cells are also described and analyzed. Conclusions. The root nodules have affinities with the Araucariales, representing the oldest record of such structures for this conifer clade. This is also the first record of nodules harboring arbuscular mycorrhizal fungi for the Jurassic; it extends our knowledge of the fossil record for this particular type of fungal association.